Diet followed by the Spanish wrestling team during a stay in the CAR of Sierra Nevada preparing the Olympics Games in Beijing - Mariscal-Arcas, M.; Fernández de Alba, M. C.; Domingo, A.; Lahtinen, J.; Martin, T.; Moraleda, L.; Rivas, A. (Archivos de medicina del deporte, 2008)
Introduction and objective: The aimed of sport nutrition is to applied the nutritional and food science principles to improved sport performance. An optimal diet is essential to preservation the health of the athlete. Nutritional assessment of the elite sportsmen study the food consumption to determinate if the diet is adequate for a good health and the energy needs associated with training and sport. Altitude Sport training is a technique commonly used in elite sport. This is a complex technique that should be carefully prepared and planned, including diet. Sportsmen with a bad diet cannot have a good performance. Material and method: This follow-up gathered diet data followed for the Spanish Wrestling Team in their sport stay in the CAR of Sierra Nevada preparing the Olympics Games in Beijing using a specific Diet Register created by the research team for sportspeople resident at the CAR of Sierra Nevada, in which the daily intake of all foods was recorded. The food composition tables of the national "Alimentación y Salud" programme were used for the nutritional evaluation of reported data. SPSS 15.0 software was used for the statistical study. Results: The study population included 5 wrestler elite athletes (3 males and 2 females), mean age was 21.5yrs (SD: 2.9). Males BMI mean was 25.1Kg/m2 (SD:2.2) and 24.4Kg/m2 (SD: 1.8) for females. Mean of energy intake was 3832.1Kcal/d (SD:1030.8), 196.4g/d (SD:48.5) from protein, 457.3g/d (SD:153.0) from carbohydrates, 144.5g/d (SD: 41.3) from lipids for males and 3415.1Kcal/d (SD:727.1), 158.4g/d (SD: 28.9) from protein, 425.1g/d (SD: 114.4) from carbohydrates, 128.5g/d (SD: 38.3) from lipids for females. Comparison of the daily energy intake, nutrients and gender (Student`s t test) showed not signifi cant differences. There is no correlation between BMI and energy consumption. Conclusion: The study population has a similar nutritional intake. We don`t find different for wrestler males and females. These athletes are conditioned by the weight competition and should be considered for the nutritional planning.